Social Determinants of Cervical Cancer Screening among Women Aged 35-64: A Quantitative Analysis of the Demographic and Health Survey Data, Haiti, 2016-2017 - Jacques W. Clerville; Darius L. Fenelon; Rajat D. Gupta (Social Medicine Publication Group, 2024)
Objective: The objective of the study is to identify the social determinants of cervical cancer screening among women aged 35-44 in Haiti. Methods: We used Haiti's Demographic and Health Survey data to identify social determinants of cervical cancer screening in Haiti among women aged 35-64. Results: We found that higher education attainment and household wealth were significantly associated with cervical cancer screening: higher education (AOR = 4.94, CI: 2.46-9.89) and secondary education (AOR = 2.28, CI:1.44-3.61); "richest" (AOR = 8.15, CI:3.97-16.72), "richer" (AOR = 4.38, CI:2.23-8.59), and "middle" (AOR =2.90, CI:1.53-5.49). Conclusion: Cervical cancer screening efforts should prioritize disadvantaged groups to address health disparities, strengthen access to screening, and provide optimal care.